16-Channel Hybrid WDM-PDM-MDM (de) Multiplexer for Multi-Band Large-Capacity Optical Transmission System Based on Thick Si $_{3}$ N $_{4}$ Platform - Deyue Ma; Xiwen He; Chen Zhou; Mingyue Xiao; Jiqiao Liu; Weibiao Chen; Zhiping Zhou (IEEE Photonics Journal, 2024)
We propose a novel design of hybrid multi-band wavelength/polarization/mode (de)multiplexer based on 800 nm thick Si $_{3}$ N $_{4}$ platform. The 16 channels are enabled by asymmetric rib polarization beam splitters, subwavelength polarization rotators and asymmetric directional couplers, consisting of two operating frequency bands, dual polarization and four transmission modes (2 $× 2×$ 4). A broad bandwidth range from 930 nm to 1600 nm is supported simultaneously on a same chip. This chip can achieve low insertion loss and crosstalk in the 100 nm range near the center wavelength (1550 nm and 980 nm). Our results demonstrate that all channels of the (de)multiplexer have an average insertion loss of less than −1.1 dB. In addition, the crosstalk in the same band is less than −20 dB, while less than −15 dB in different frequency bands. This hybrid (de)multiplexer chip has a great potential for application in multi-band large-capacity optical communication systems, especially in integrated multi-band (de)multiplexing systems.